Minimising risk of early-age thermal cracking and delayed ettringite formation in concrete – A hybrid numerical simulation and genetic algorithm mix optimisation approach. (13th September 2021) - Chiniforush, Alireza A.; Gharehchaei, Maryam; Akbar Nezhad, Ali; Castel, Arnaud; Moghaddam, Farzad; Keyte, Louise; Hocking, David; Foster, Stephen
Highlights: Numerical simulation of hydration heat transfer and thermal cracking in early-age concrete. Hybrid mix design optimization of mass concrete casting with the Genetic Algorithm. Minimizing risk of early-age thermal cracking and delayed ettringite formation (DEF) Abstract: Early-age thermal cracking and delayed ettringite formation (DEF) are major durability risks associated with mass concrete casting with high cement content. Among various strategies to mitigate the risk of early-age thermal cracking and DEF, concrete mix optimisation is favoured by the industry due to its minimal required operational adjustments and insignificant implementation cost. The existing concrete mix design optimization methods are, however, incapable of accounting for the risk of early-age thermal cracking and DEF; and have been designed solely to meet the mechanical performance targets. Mitigating the risk of DEF could be challenging mainly because limiting the temperature rise in concrete requires moderating the hydration heat/rate to minimize the risk of early-age thermal cracking and DEF which could contradict the traditional objectives associated with the concrete's mechanical performance. Further, early-age thermal cracking can be influenced by project-specific factors including the dimensions of the concrete element, ambient conditions, and external restraints which do not come into the picture in a conventional mix design approach. These issues add to the complexity of the mix design problem. This paper presents a mix design approach based on integrated numerical simulation of heat transfer in concrete and genetic algorithm optimisation that minimises the risk of early-age cracking within the limits specified for the mechanical performance of concrete. The results of the optimization framework applied to three case studies show a significant decrease in peak temperature, as well as the ratio of induced tensile stresses to developed tensile strength for optimized concrete mixes.